2020
DOI: 10.1536/ihj.19-574
|View full text |Cite
|
Sign up to set email alerts
|

Poor Long-Term Survival of Out-of-Hospital Cardiac Arrest in Children

Abstract: The effect of post-cardiac arrest care in children with out-of-hospital cardiac arrest (OHCA) has not been adequately established, and the long-term outcome after pediatric OHCA has not been sufficiently investigated. We describe here detailed in-hospital characteristics, actual management, and survival, including neurological status, 90 days after OHCA occurrence in children with OHCA transported to critical care medical centers (CCMCs). We analyzed the database of the Comprehensive Registry of Intensive Care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…All TOR rules in this study showed highly accurate PPVs and specificity for unfavorable neurological outcomes, similar to studies in adults. 1 , 7 , 14 , 15 Studies of pOHCA are limited, and the ALS and BLS TOR rules, which have been evaluated in the past, have shown high accuracy in predicting unfavorable neuroprognosis, 8 similar to this study.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…All TOR rules in this study showed highly accurate PPVs and specificity for unfavorable neurological outcomes, similar to studies in adults. 1 , 7 , 14 , 15 Studies of pOHCA are limited, and the ALS and BLS TOR rules, which have been evaluated in the past, have shown high accuracy in predicting unfavorable neuroprognosis, 8 similar to this study.…”
Section: Discussionsupporting
confidence: 74%
“…Pediatric out-of-hospital cardiac arrest (pOHCA) has an unfavorable prognosis, with only 6–8% of patients being discharged from the hospital and only 1–2% experiencing favorable neurological outcomes among those who survive. 1 , 2 , 3 Pediatric patients typically survive longer, making decisions regarding the termination of resuscitation (TOR) ethically complex. 4 Therefore, accurate prognosis prediction is crucial for determining a treatment plan that aligns with the family’s preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, the outcome is often poor and the consequences are devastating for both the family and the community. 4,5 Sudden cardiac death is responsible for approximately 5%-10% of all deaths in children 5-19 of age. 6 During a pediatric SCA, rapid access to an automated external defibrillator (AED) is critical, 7 because the survival rate of SCA in educational institutions without an action plan is as low as 10%.…”
Section: R Esum Ementioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 Of survivors, many are left with devastating neurological injury. 3 , 6 A recent epidemiological study by Fink et al found no change in incidence or survival rates of POHCA events in North America over time, highlighting the need for further investigation into this field. 5 …”
Section: Introduction / Backgroundmentioning
confidence: 99%